Persistent nucleation and size dependent attachment kinetics produce monodisperse PbS nanocrystals. Issue 17 (14th April 2022) - Abécassis, Benjamin; Greenberg, Matthew W.; Bal, Vivekananda; McMurtry, Brandon M.; Campos, Michael P.; Guillemeney, Lilian; Mahler, Benoit; Prevost, Sylvain; Sharpnack, Lewis; Hendricks, Mark P.; DeRosha, Daniel; Bennett, Ellie; et al.
Abstract : In situ X-ray scattering kinetics and population balance modeling of crystal nucleation and growth. Abstract : Modern syntheses of colloidal nanocrystals yield extraordinarily narrow size distributions that are believed to result from a rapid "burst of nucleation" (La Mer, JACS, 1950, 72 (11), 4847–4854) followed by diffusion limited growth and size distribution focusing (Reiss, J. Chem. Phys., 1951, 19, 482). Using a combination of in situ X-ray scattering, optical absorption, and 13 C nuclear magnetic resonance (NMR) spectroscopy, we monitor the kinetics of PbS solute generation, nucleation, and crystal growth from three thiourea precursors whose conversion reactivity spans a 2-fold range. In all three cases, nucleation is found to be slow and continues during >50% of the precipitation. A population balance model based on a size dependent growth law (1/ r ) fits the data with a single growth rate constant ( k G ) across all three precursors. However, the magnitude of the k G and the lack of solvent viscosity dependence indicates that the rate limiting step is not diffusion from solution to the nanoparticle surface. Several surface reaction limited mechanisms and a ligand penetration model that fits data our experiments using a single fit parameter are proposed to explain the results.